A survey of pharmacological and nonpharmacological treatment of functional gastrointestinal disorders. Issue 5 (1st October 2013) - Lahner, Edith; Bellentani, Stefano; Bastiani, Rudy De; Tosetti, Cesare; Cicala, Michele; Esposito, Gianluca; Arullani, Paolo; Annibale, Bruno
Abstract : Background: Treatment of functional gastrointestinal disorders (FGIDs) is based on symptoms relieve by conventional drugs, but increasingly complementary and alternative medicine (CAM) is used. Objective: This survey aimed to investigate the current treatments used by FGIDs patients. Methods: A total of 25 Italian gastroenterologists interviewed outpatients on gastrointestinal symptoms and treatments (pharmacological, CAM, diet/dietary supplements) used during the last year to relieve FGIDs. Consecutive adults with FGIDs according to Rome III were included. Results: Of the 199 patients, 81% used conventional drugs, 64.3% diet/dietary supplements, and 48.7% CAM. Conventional drugs, diet/dietary supplements, or CAM as exclusive treatment were used by 24.6, 6, and 2.5% of patients, respectively. Two‐thirds used more than one treatment: 34.7% conventional drugs, CAM, and diet/dietary supplements, 17.1% conventional drugs and diet/dietary supplements, 10.1% diet and CAM, and 5% conventional drugs and CAM. Benefits and adverse effects were similar for conventional drugs and nonpharmacological treatments. Males (OR 2.4) without lower GI symptoms (OR 5.4) used more frequently exclusive pharmacological treatment of FGIDs. Conclusions: Conventional drugs are the preferred treatment for FGID. CAM and dietary modifications are more likely used as an adjunct to rather than instead of conventional drugs. Adverse effects occurred in all treatments.